The range of TOEFL scores predicted by TOEP - Madya, Suwarsih; Retnawati, Heri; Purnawan, Ari; Putro, Nur Hidayanto Pancoro Setyo; Kartianom, K. (Universitas Pendidikan Indonesia, 2020)
The Indonesian Testing Service Centre (ITSC) has developed an online standardized test called TOEP (Test of English Proficiency) as a fresh alternative for measuring the test takers’ listening and reading proficiency. To ensure its quality, the TOEP scores need to be validated against the scores obtained from another established standardized test, in this case the ITP-TOEFL. This study aimed at finding out to what extent the range of scores which are measured by TOEP can predict the scores obtained from ITP-TOEFL. A quantitative approach was applied in this study, focusing on the analysis of scores obtained by 1,048 people taking TOEP in 2016, 2017, and 2019 and 383 testees had taken both TOEP and ITP-TOEFL. A regression analysis was conducted to establish the prediction equation of TOEP to ITP-TOEFL. The range of scores of proficiency measured through TOEP was estimated using the advanced item response theory, especially the information function value. The results of analysis show that TOEP can predict test takers’ English proficiency in the range of minimum 310 and maximum 656.34 at the ITP-TOEFL scales. It can be concluded that TOEP has a good predictive validity to ITP-TOEFL.